2000
DOI: 10.1073/pnas.080536597
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-1 conjugation to topoisomerase I: A possible repair response to topoisomerase-mediated DNA damage

Abstract: Ubiquitin͞26S proteasome-dependent degradation of topoisomerase I (TOP1) has been suggested to be a unique repair response to TOP1-mediated DNA damage. In the current study, we show that treatment of mammalian cells or yeast cells expressing human DNA TOP1 with camptothecin (CPT) induces covalent modification of the TOP1 by SUMO-1͞Smt3p, a ubiquitin-like protein. This conclusion is based on the following observations: (i) Mammalian DNA TOP1 conjugates induced by CPT were cross-reactive with SUMO-1͞Smt3p-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
148
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(161 citation statements)
references
References 54 publications
9
148
1
Order By: Relevance
“…These results suggest that Lys-117 is the major sumoylation site on TOP1, and that the sumoylation of the sites flanking Lys-117 is sufficient to enable TOP1 to be cleared from nucleoli in response to CPT and to prevent the accumulation of TOP1 in nucleoli under basal conditions. Mutation of only a single lysine (Lys-117) eliminated the majority of sumoylated TOP1 despite the fact that up to six SUMO molecules have been seen attached to TOP1 (2,20). These observations can be explained by more than one model.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results suggest that Lys-117 is the major sumoylation site on TOP1, and that the sumoylation of the sites flanking Lys-117 is sufficient to enable TOP1 to be cleared from nucleoli in response to CPT and to prevent the accumulation of TOP1 in nucleoli under basal conditions. Mutation of only a single lysine (Lys-117) eliminated the majority of sumoylated TOP1 despite the fact that up to six SUMO molecules have been seen attached to TOP1 (2,20). These observations can be explained by more than one model.…”
Section: Discussionmentioning
confidence: 80%
“…Currently, the multiple monosumoylation model appears to be most consistent with our experimental data and with the fact that single SUMO conjugates on four closely spaced (IVL)KXE sites have been mapped on Cdc3 (25). Notably, using antibodies specific to SUMO-1 or SUMO-2/3, we and others have observed SUMO-2/3 and SUMO-1 conjugated to TOP1 (20,21). 3 The close juxtaposition of multiple sumoylation sites on TOP1 (Lys-103, Lys-117, Lys-153) is similar to that found on the Saccharomyces cerevisiae septins Cdc3 (Lys-4, Lys-11 , Lys-30, Lys-63) and Shs/Sep7 (Lys-426, Lys-437) (25), the cytomegalovirus protein IE2 (Lys-175, Lys-180) (26), HDAC1 (Lys-444, Lys-476) (27), and GRIP1 (Lys-731, Lys-788) (28) (see Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolar Targeting of Topoisomerase I Does Not Depend on the Presence of the Major Sumoylation Site-It has been shown that camptothecin stimulates modification of topo I with ubiquitin (18) and SUMO (13) and that these modifications play a crucial role in resistance of tumor cells to camptothecin, because they trigger proteolytic degradation of DNA-linked topo I (40). Thus, it is clear that both effects are important cellular responses to topo I-mediated DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, partitioning of topo I between nucleoli and nucleoplasm seems in general governed by mobility gradients within the cell nucleus, with nucleolar accumulation reflecting the enzyme's lesser mobility in the nucleoli, and relocation to the nucleoplasm in response to camptothecin reflecting attenuation of the enzyme at nucleoplasmic sites, where it is actively processing genomic DNA (12). However, this simple explanation was disputed, because camptothecin also stimulates modification of topo I with small ubiquitin-like modifiers (SUMO) (13), and mutational silencing of the major target site of topo I for this modification (K103R,K117R,K153R) enhances nucleolar accumulation of the enzyme and abolishes its nucleolar clearance in response to camptothecin (14). This has been interpreted as an indication of an active and directed transport of topo I between nucleoli and nucleoplasm that is triggered by the attachment of SUMO to (sumoylation of) the enzyme.…”
mentioning
confidence: 99%
“…SUMOplot analysis predicted that human TOP1 contains 12 motifs that have high probabilities for SUMOylation, and TOP1 has been shown to be poly-SUMOylated at K103, K117 and K153 in response to CPT [23][24][25][26] . However, we found that transcriptionassociated TOP1 SUMOylation is distinct from the SUMOylation events induced by CPT.…”
Section: Top1 Is Sumoylated At K391 and K436 During Transcriptionmentioning
confidence: 99%